Preface - Życzkowski, M. (Archives of Mechanics, 2005)
Hundred years ago M.T. Huber published his fundamental paper “Specific work of strain as a measure of material effort”, forming the basis of modern theory of plasticity and of the related branches of mechanics of materials and structures. The paper, written in Cracow, was published in Polish in the journal “Czasopismo Techniczne”, Lwów 1904, and was scarcely accessible to a broader circle of scientists. The early dissemination of his ideas is mainly due to quotation in A. and L. Föppl’s book “Drang und Zwang”,München 1920, and to a discussion between Huber, Mises, and Hencky during the First Congress of Mechanics in Delft 1924. Full English translation of the paper has been published just recently in Archives of Mechanics 56, 3, 173–190, 2004.